Factors shaping intersectoral action in primary health care services. (6th November 2014) - Anaf, Julia; Baum, Fran; Freeman, Toby; Labonte, Ron; Javanparast, Sara; Jolley, Gwyn; Lawless, Angela; Bentley, Michael
Abstract Objective: To examine case studies of good practice in intersectoral action for health as one part of evaluating comprehensive primary health care in six sites in South Australia and the Northern Territory. Methods: Interviews with primary health care workers, collaborating agency staff and service users (Total N=33); augmented by relevant documents from the services and collaborating partners. Results: The value of intersectoral action for health and the importance of partner relationships to primary health care services were both strongly endorsed. Factors facilitating intersectoral action included sufficient human and financial resources, diverse backgrounds and skills and the personal rewards that sustain commitment. Key constraining factors were financial and time limitations, and a political and policy context which has become less supportive of intersectoral action; including changes to primary health care. Conclusions: While intersectoral action is an effective way for primary health care services to address social determinants of health, commitment to social justice and to adopting a social view of health are constrained by a broader health service now largely reinforcing a biomedical model. Implications: Effective organisational practices and policies are needed to address social determinants of health in primary health care and to provide a supportive context for workers engaging in intersectoral action.